2005
DOI: 10.1111/j.1600-0609.2004.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hb Q‐Thailand with homozygous Hb E and heterozygous Hb Constant Spring in pregnancy

Abstract: Hemoglobin (Hb) Q-Thailand [alpha74(EF3): Asp-->His] is an abnormal Hb found mainly in China and South-east Asian countries. Association of the alpha(Q-Thailand) allele with alpha-thalassemia has important implications in diagnosis. We report the hitherto undescribed conditions of this variant in two unrelated pregnant Thai women. Routine Hb analyses using high-performance liquid chromatography identified abnormal Hb migrating after Hb A(2) in addition to a homozygous Hb E in the proband 1 and to a heterozygou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 21 publications
4
15
0
Order By: Relevance
“…Peak of Hb H and Hb Bart's were not found on HPCL and CE analysis. The previous studies showed that patients with compound heterozygous of Hb CS and Hb Q-Thailand had mild hypochomic microscytic anemia [4,15] and it was consistent with the present study which showed that a patient had low levels of Hb and MCV. However, patients in the present study had a higher MCV than the patients with the compound heterozygous of Hb CS and Hb Q-Thailand who were reported by Singsanan et al, and it was quite similar to the MCV of 26 patients with heterozygous of Hb Q-Thailand [4].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Peak of Hb H and Hb Bart's were not found on HPCL and CE analysis. The previous studies showed that patients with compound heterozygous of Hb CS and Hb Q-Thailand had mild hypochomic microscytic anemia [4,15] and it was consistent with the present study which showed that a patient had low levels of Hb and MCV. However, patients in the present study had a higher MCV than the patients with the compound heterozygous of Hb CS and Hb Q-Thailand who were reported by Singsanan et al, and it was quite similar to the MCV of 26 patients with heterozygous of Hb Q-Thailand [4].…”
Section: Discussionsupporting
confidence: 93%
“…The molecular analysis for detection of a-thalassemia-1 Southeast Asian (SEA) type deletion and Hb CS was performed by using real-time PCR with SYBR Green1 high resolution melting (HRM) analysis as previously described [13,14]. The multiple allele specific polymerase chain reaction (ASPCR) was also performed for molecular diagnosis of Hb Q-Thailand as previously described [4,15].…”
Section: Dna Preparation and Molecular Analysismentioning
confidence: 99%
“…Globin gene mutations causing high Hb F levels, including δβ thalassemia, HPFH-6, and deletion-inversion G γ( A γδβ) 0 -thalassemia, were also investigated in suspected cases. Polymerase chain reaction (PCR) techniques as described previously (either Gap PCR or allele-specific PCR) were used for DNA analysis [12][13][14][15][16][17] .…”
Section: Methodsmentioning
confidence: 99%
“…In fact, it is not unexpected that tetrameric assembly of these globin chain variants could generate some uncommon Hb variants which might complicate laboratory diagnostics. Interactions of the α Q-Thailand -globin chain with β A -, β E -, δ-, and γ-globin chains subsequently lead to the formation of Hb Q-Thailand (α QT 2 β A 2 ), Hb QE (α QT 2 β E 2 ), Hb QA 2 (α QT 2 δ 2 ), and Hb QF (α QT 2 γ 2 ), respectively, with different HPLC and capillary electrophoretic profiles [9,13,14,15]. As shown in figure 1, we detected as many as 5 Hb variants in the two Thai patients with double heterozygosity for Hb Q-Thailand and Hb Tak, including Hb Q-Thailand (α QT 2 β A 2 ), Hb Tak (α A 2 β Tak 2 ), Hb QA 2 (α QT 2 δ 2 ), Hb QF (α QT 2 γ 2 ), and a novel variant, i.e.…”
Section: Discussionmentioning
confidence: 99%